2015
DOI: 10.1002/jbm.a.35462
|View full text |Cite
|
Sign up to set email alerts
|

Peptide gel in a scaffold as a composite matrix for endothelial cells

Abstract: The performance of a composite environment with human umbilical vein endothelial cells (HUVECs) has been studied to provide an in vitro proof of concept of their potential of being easily vascularized. These cells were seeded in 1 mm thick scaffolds whose pores had been filled with a self-assembling peptide gel, seeking to improve cell adhesion, and viability of these very sensitive cells. The combination of the synthetic elastomer poly(ethyl acrylate), PEA, scaffold and the RAD16-I peptide gel provides cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…Among the wide variety of SAPs, RAD16‐I is a multiple of the RADA aminoacid sequence. We have previously shown that the incorporation of RAD16‐I in the scaffolds pores favors endothelial cell adhesion, survival, and migration in vitro and improves the uniformity of the seeded cells in them …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the wide variety of SAPs, RAD16‐I is a multiple of the RADA aminoacid sequence. We have previously shown that the incorporation of RAD16‐I in the scaffolds pores favors endothelial cell adhesion, survival, and migration in vitro and improves the uniformity of the seeded cells in them …”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the incorporation of RAD16-I in the scaffolds pores favors endothelial cell adhesion, survival, and migration in vitro and improves the uniformity of the seeded cells in them. 34,35 PEA-based scaffolds presenting two different porous architectures (with orthogonal cylinders or with spherical interconnected pores) were combined in this work with the RADA16-I peptide gels. As regards vascularization of the scaffolds, the shape, size, and connectivity of the pore structure can be of critical importance, since they define the overall geometrical constraints for the formation of tubularlike networks within the constructs.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the aqueous HPE was encapsulated in a novel nanocomposite gel fiber (16,17) prepared by the ideal formulation of IKVAV, RGD, RAD16 and FGL-PA through LbL self-assembly (17,18,19,20), and the morphology, particle size, drug loading, drug release efficacy, encapsulation rate and structure validation were examined. IKVAV is an amphiphilic molecule, also known as isoleucine-lysine-valine-alanin-valine.…”
Section: Introductionmentioning
confidence: 99%
“…Herein we have targeted the characterization at a nanometric scale of the interaction between this SAP and the acrylic substrate used to produce the scaffolds and a 90/10 wt poly(ethyl acrylate-co-acrylic acid) copolymer as more hydrophilic material [19]. The interaction between PEA substrates and extracellular matrix proteins such as fibronectin [20,21] or laminin [22] has already been characterized: PEA has been found to favor the adhesion of these proteins and to facilitate the formation of a protein network that contributes to increase subsequent cell adhesion despite the hydrophobicity of the material.…”
Section: Introductionmentioning
confidence: 99%